1987
DOI: 10.1007/bf00289391
|View full text |Cite
|
Sign up to set email alerts
|

Anther culture of maize and the visualization of embryogenic microspores by fluorescent microscopy

Abstract: Three maize genotypes previously shown in the literature to respond to anther culture were tested under various conditions. Studies indicated that embryogenic response ranged from 0 to 100 embryos per 1,000 anthers plated and was significantly lower without cold pretreatment of the anthers. Culture in liquid media tended to produce more embryos than in semi-solid as did the addition of activated charcoal to either liquid or solid culture media. Most results were confounded by plant-to-plant variation which ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Flower bud whose corolla is slightly larger than sepals contain microspores having partial anthocynin colouration are said to be of later stages (Mityko et al, 1995;Novak, 1974;Morrison et al, 1986a). Dolcet-Sanjuan et al (1997) confirmed the development stage of microspores (10% binucleate) using the method by Pace et al (1987), by staining with mithramycin A. DAPI staining was also done for best stage determination (Coleman and Goff, 1985). Lantos et al (2009) has experimented with collected buds of late uninucleate and early binucleate stages of microspore development for effective embryogenesis to occur in C. annuum.…”
Section: Microspore Developmental Stagementioning
confidence: 93%
“…Flower bud whose corolla is slightly larger than sepals contain microspores having partial anthocynin colouration are said to be of later stages (Mityko et al, 1995;Novak, 1974;Morrison et al, 1986a). Dolcet-Sanjuan et al (1997) confirmed the development stage of microspores (10% binucleate) using the method by Pace et al (1987), by staining with mithramycin A. DAPI staining was also done for best stage determination (Coleman and Goff, 1985). Lantos et al (2009) has experimented with collected buds of late uninucleate and early binucleate stages of microspore development for effective embryogenesis to occur in C. annuum.…”
Section: Microspore Developmental Stagementioning
confidence: 93%
“…Microspore viability was measured after isolation using the fluorescent stain, FDA (fluorescein diacetate - Pace et al 1987) and recorded as the number of viable and nonviable cells (FDA counts) and converted to a percentage for analysis. To determine the isolation procedure which gave the highest viability, four isolation procedures (blending, floating, macerating and stirring), and either pre-isolation mannitol conditioning or no mannitol conditioning (4 x 2 ~ 8 isolation treatments) were evaluated.…”
Section: Microspore Viability Measurementmentioning
confidence: 99%
“…Such an exact differentiation was not always possible in the acetocarmine stained samples (Henry et al 1984). The application of DNA-specific fluorescent dyes in different fields of pollen biology (Coleman and Golf 1985;Hough et al 1985;Vergne et al 1987) and biotechnology (Kyo and Harada 1986;Pace et al 1987) is very advantageous.…”
Section: Discussionmentioning
confidence: 99%